2002
DOI: 10.1007/s00259-002-0886-2
|View full text |Cite
|
Sign up to set email alerts
|

Persistent non-specific FDG uptake on PET imaging following hip arthroplasty

Abstract: Hip arthroplasty is a common surgical procedure, but the diagnosis of infection associated with hip arthroplasty remains challenging. Fluorine-18 fluoro-2-deoxy-D-glucose positron emission tomography (FDG-PET) has been shown to be a promising imaging modality in settings where infection is suspected. However, inflammatory reaction to surgery can result in increased FDG uptake at various anatomic locations, which may erroneously be interpreted as sites of infection. The purpose of this study was to assess the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
84
1
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(92 citation statements)
references
References 23 publications
3
84
1
4
Order By: Relevance
“…More knowledge about the incidence and pattern of nonspecific FDG uptake around knee prostheses may improve the specificity of FDG-PET in detecting prosthetic knee joint infection. Despite the findings of Zhuang et al [33], our subgroup analysis did not reveal any significantly higher sensitivity or specificity among studies which used FDG uptake at the BPI as criterion for positivity, while emphasizing that FDG uptake limited to the soft tissues or adjacent to the neck of the prosthesis was not considered suggestive of infection (Table 8). Metallic prosthetic material can cause artifacts on attenuation-corrected FDG-PET images and may also affect diagnostic performance.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…More knowledge about the incidence and pattern of nonspecific FDG uptake around knee prostheses may improve the specificity of FDG-PET in detecting prosthetic knee joint infection. Despite the findings of Zhuang et al [33], our subgroup analysis did not reveal any significantly higher sensitivity or specificity among studies which used FDG uptake at the BPI as criterion for positivity, while emphasizing that FDG uptake limited to the soft tissues or adjacent to the neck of the prosthesis was not considered suggestive of infection (Table 8). Metallic prosthetic material can cause artifacts on attenuation-corrected FDG-PET images and may also affect diagnostic performance.…”
Section: Discussioncontrasting
confidence: 53%
“…Increased FDG uptake around the distal tip of the hip prosthesis is also nonspecific. However, FDG uptake along the interface between bone and hip prosthesis is virtually never seen in asymptomatic patients or in those with aseptic loosening and is, therefore, highly suggestive of infection [33]. Persistently increased nonspecific FDG uptake following knee arthroplasty has also been mentioned [33], but should be further investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An important case of false-positive reaction is related to the hip arthroplasty. A retrospective and prospective study conducted by Zhuang et al (2002) with 710 patients and 9 patients respectively, concluded that, following hip arthroplasty, non-specifically increased FDG uptake around the head or neck of the prosthesis persists for many years, even in patients without any complications. Therefore, to minimize the number of false-positive results with PET studies, caution should be exercised when interpreting FDG uptake around the head or neck portion of prostheses.…”
Section: Infection/inflamationmentioning
confidence: 99%